The effect of anthracene derivatives on the state of the extracellular matrix of the periodontal connective tissue and the oral mucosa of old rats - N. N. Savelieva; O. V. Suslova; S. A. Schneider; E. K. Tkachenko (Kazimierz Wielki University, 2019)
In the experiments on 27 old female rats, the effect of the anthracene derivative preparation on the state of the intercellular matrix of the connective tissue of the periodontal and oral mucosa in intact animals, as well as on the periodontitis model, was studied.